Sustainable Material Selection Framework for Temporary Infrastructure in Goa - Vashum, Yaoyo (Journal of Progress in Civil Engineering, 2026)
Coastal zones are vital ecological and economic resources globally, offering rich biodiversity, supporting livelihoods, and acting as natural buffers against climate - related disasters. However, these fragile ecosystems face threats from unsustainable development, including unregulated tourism - related infrastructure. Temporary structures play a critical role in supporting tourism while minimizing permanent impacts. This paper explores sustainable materials such as bamboo, FSC - certified timber, geotextiles, recycled steel, and mycelium composites for temporary structures in Coastal Regulation Zones (CRZs). The research highlights the unique challenges faced by states like Goa, where the tourism sector not only contributes significantly to the economy but also places immense pressure on coastal ecosystems. With millions of visitors each year, Goa's demand for temporary structures necessitates a careful approach to construction that respects ecological balances. By focusing on sustainable materials and practices, this study aims to reduce environmental impact while providing flexible solutions that accommodate seasonal tourism. Supporting this exploration, an analysis of India's CRZ regulations is provided, alongside international examples from Bali, Indonesia; the Maldives; and Scotland, which delve into best practices for balancing tourism development and environmental protection. By integrating global insights, innovative materials, and local legal contexts, this comprehensive review offers a roadmap for sustainable development in coastal areas using structures that are both ecologically sound and economically viable. Visuals, including maps and material illustrations, enhance the reader's understanding of sustainable construction approaches in fragile coastal ecosystems. Ultimately, this research aims to empower communities, promote disaster resilience, and support responsible tourism growth that aligns with the environmental and socio - cultural values of Goa and similar coastal regions.